Strong boundary values, analytic functionals, and nonlinear Paley-Wiener theory - Rosay, Jean-Pierre, 1945- (Memoirs of the American Mathematical Society, 2001)
Introduction Preliminaries on analytic functionals and hyperfunctions Appendix on good compact sets Analytic functionals as boundary values Nonlinear Paley-Wiener theory Strong boundary values Strong boundary values for the solutions of certain partial differential equations Comparison with other notions of boundary values Boundary values via cousin decompositions The Schwarz reflection principle References Index of notions.